Research of the Influence of Rotation Speed on Lubricating Property of Sliding Bearing with Oil Seal Edge - Wentao Zhang; Hao Kong (Jixie chuandong)
The numerical analysis method is used to establish the one-way fluid structure coupling model of sliding bearing with oil seal edge structure， and the sliding bearing lubrication performance and bearing pad deformation are analyzed at different speeds. The results show that the oil film bearing capacity， pressure peak value， temperature and wall shear stress of the sealed oil edge sliding bearing are higher than unsealed oil seal edge sliding bearing， gas phase volume fraction， friction factor and outlet leakage flow are all smaller than oil unsealed edge sliding bearings， and the oil film bearing capacity， pressure peak and temperature are increased with the increase of rotating speed. The deformation of sliding bearing bush is mainly affected by temperature， the deformation of bearing pad with oil sealing edge is larger than without oil sealing edge， and the deformation of bearing bush are increased with the increase of rotating speed.